ChemInform Abstract: A Trinuclear Zn3(OAc)4‐3, 3′‐bis(aminoimino)binaphthoxide Complex for Highly Efficient Catalytic Asymmetric Iodolactonization. Issue 52 (29th December 2014) - Arai, Takayoshi; Sugiyama, Noriyuki; Masu, Hyuma; Kado, Sayaka; Yabe, Shinnosuke; Yamanaka, Masahiro
Abstract Resulting products are obtained with excellent enantioselectivities.